Biomaterials science and tissue engineering : principles and methods - Basu, Bikramjit (Cambridge University Press, 2017)
"Provides an encyclopedic coverage of biomaterials science which, at the same time, has enough to interest the biomedical scientists and engineers"--Resumé vydavatele
Keywords: biologické materiály; tkáňové inženýrství; biomedicína; biomedicínské inženýrství; biokompatibilita; cytologie; biological materials; tissue engineering; biomedicine; biomedical engineering; biocompatibility; cytology; učebnice vysokých škol; případové studie; textbooks (higher); case studies